Association of telomere length with chronic exposure to ionizing radiation among inhabitants of natural high background radiation areas of Ramsar, Iran - Movahedi, Anahita; Mostajaboddavati, Mojtaba; Rajabibazl, Masoumeh; Mirfakhraie, Reza (International Journal of Radiation Biology, 2019)
Purpose: There are few areas in the world where ionizing radiation (IR) dose received by the public from radon gas and other radioactive elements are much higher than recommended limits. Telomere length is a potential biomarker of genomic instability due to oxidative stress from IR exposure. In this study, we investigated the impact of chronic exposure to environmental IR on relative telomere length (RTL) in white blood cells (WBC) among inhabitants of high background radiation areas (HBRA) of Ramsar, Iran. Materials and methods: One hundred and four individuals from HBRAs of Ramsar and 104 age-matched subjects from normal background radiation areas (NBRA) of Iran were enrolled in the study. The RTLs of WBC DNA samples were measured by a quantitative polymerase chain reaction (q-PCR) approach. Results: Mean RTL in HBRA and NBRA groups did not show any significant difference (1.21 ± 0.71 versus 1.22 ± 0.66, p = .306). After controlling for all demographic variables, less than 1% of the variances in RTL values were related to background radiation exposure. Conclusion: We conclude that chronic exposure to natural IR has no statistically significant effect on RTL among the inhabitants of HBRAs of Ramsar compared with a control grou
Keywords: Ramsar; natural background radiation; relative telomere length; radon

Identification of putative G-quadruplex DNA structures in S. pombe genome by quantitative PCR stop assay - Jamroskovic, Jan; Obi, Ikenna; Movahedi, Anahita; Chand, Karam; Chorell, Erik; Sabouri, Nasim (DNA Repair, 2019)
In order to understand in which biological processes the four-stranded G-quadruplex (G4) DNA structures play a role, it is important to determine which predicted regions can actually adopt a G4 structure. Here, to identify DNA regions in Schizosaccharomyces pombe that fold into G4 structures, we first optimized a quantitative PCR (qPCR) assay using the G4 stabilizer, PhenDC3. We call this method the qPCR stop assay, and used it to screen for G4 structures in genomic DNA. The presence of G4 stabilizers inhibited DNA amplification in 14/15 unexplored genomic regions in S. pombe that encompassed predicted G4 structures, suggesting that at these sites the stabilized G4 structure formed an obstacle for the DNA polymerase. Furthermore, the formation of G4 structures was confirmed by complementary in vitro assays. In vivo, the S. pombe G4 unwinder Pif1 helicase, Pfh1, was associated with tested G4 sites, suggesting that the G4 structures also formed in vivo. Thus, we propose that the confirmed G4 structures in S. pombe form an obstacle for replication in vivo, and that the qPCR stop assay is a method that can be used to identify G4 structures. Finally, we suggest that the qPCR stop assay can also be used for identifying G4 structures in other organisms, as well as being adapted to screen for novel G4 stabilizers.<br
Keywords: G-quadruplex; DNASchizosaccharomyces pombe; G4 stabilizer PhenDC3; Pif1 family helicase Pfh1; DNA replication; Quantitative PCR